2015
DOI: 10.1111/jnc.13393
|View full text |Cite
|
Sign up to set email alerts
|

Antiretrovirals inhibit arginase in human microglia

Abstract: Preliminary evidence in an animal model, that is, primary cultures of rat microglia cells, suggested that some antiretroviral drugs (ARVs), namely darunavir, atazanavir, efavirenz, and nevirapine, increase NO production through a mechanism involving the inhibition of arginase (ARG) activity. This study was conceived to investigate the effects of ARVs on ARG activity in a human experimental model. We compared CHME-5 human microglial immortalized cells under basal conditions with cells exposed to either IL-4, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This is not surprising as it has been characterized that CHME-5 cells require a cytomix formula (e.g. interferon-c, TNF-a, IL1-b) to produce proinflammatory substances such as nitric oxide [25]. Furthermore, by using rat-specific gRNAs and PCR assays in our experiments, we confirmed that CHME-5 cells are derived from rat.…”
Section: Discussionsupporting
confidence: 83%
“…This is not surprising as it has been characterized that CHME-5 cells require a cytomix formula (e.g. interferon-c, TNF-a, IL1-b) to produce proinflammatory substances such as nitric oxide [25]. Furthermore, by using rat-specific gRNAs and PCR assays in our experiments, we confirmed that CHME-5 cells are derived from rat.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to the HMC3/CHME3 aliquots, increased iNOS expression and NO production was detected also after overexpression of the endogenous retrovirus W envelope protein [88] and in response to a mixture of pro-inflammatory cytokines, including TNFα, IL-1β, and IFNγ [106]. Furthermore, the CHME-5 cells displayed increased arginase (ARG) activity in response to IL-4, which was significantly reduced by several antiretroviral drugs [106].…”
Section: The Human Microglial Chme-5 Cell Linementioning
confidence: 99%
“…LPSinduced NF-κB p65 activation was consistent with other microglial cell lines [28,[37][38][39] . Given the fact that many studies investigating microglial responses used the same dose of LPS (1 μg/mL), we are confident that CHME-5 cells were adequately treated to observe inflammatory responses [36,40,41] ; unlike the use of a lower dose of LPS (1 ng/mL), which failed to activate and release nitric oxide in CHME-5 cells [42] . Additionally, other studies using human primary microglia and CHME-5 cells have used similar LPS dose range (0.1-1 μg/mL) and time points (6 h for RT-PCR) to investigate inflammatory responses [26,36,37,40,41] .…”
Section: Discussionmentioning
confidence: 91%